Transforming Protein Consumption Patterns: The Role Of Chicken Eggs Among Pattimura University Students - Nafly Comilo Tiven; Tienni Mariana Simanjorang (International Journal of Business and Quality Research, 2026)
This study aims to analyze the role of chicken eggs as an alternative source of protein in the consumption patterns of Pattimura University students. Although the protein consumption of the Indonesian people has been sufficient in quantity, the contribution of animal protein other than fish and meat is still limited. Chicken eggs are a potential choice because they are affordable, highly nutritious, and easy to obtain. The study used a quantitative approach with a descriptive survey method of 120 respondents selected by purposive sampling. Data were collected through questionnaires and analyzed descriptively. The results show that the majority of students consume eggs 1–2 times per week. The main reasons for consumption are affordable prices (41.70%) and ease of processing (29.20%). Most respondents have a positive perception that eggs can replace meat and fish protein and meet daily protein needs. The main factor that affects consumption is price, followed by availability, practicality, and nutritional knowledge. Chicken eggs play an important role as an alternative source of protein for students, especially in conditions of economic limitations, although nutrition education is still needed to increase the diversity of protein consumption.